Genetic Determinants of High-Level Oxacillin Resistance in Methicillin-Resistant Staphylococcus aureus - Pardos de la Gandara, Maria (2019)
Free PMC Article: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5971597/